Leadership in Action Making Sure that a Team is the Right Way to Go - Kanaga, Kim (Center for Creative Leadership, 2001)
Leaders can apply several criteria to determine whether a team is the right tool for meeting a business goal.
Title from content provider
Keywords: Leadership; Teams in the workplace; Organizational behavior; Équipes de travail; Comportement organisationnel